Dietary fiber in reducing of elevated blood lead concentration in children - Hnida, Natalia I.; Гніда, Наталя Ігорівна; Hnidoi, Ihor M.; Гнiдой, Iгор Михайлович (My University, 2023)
The aim of the study was to evaluate the effectiveness of dietary fiber in reducing elevated blood lead concentration (BLC) of Ukrainian children. Materials and methods. 80 random children aged 4 to 15 years were examined. The lead content in venous blood was detected by atomic absorption spectrometry with electro-thermal atomizer (ET AAS). Indicators of morphological and biochemical blood tests were determined by generally accepted methods. Results. About a quarter of the children had BLC ≥ 5μg/dL. They had a higher content of eosinophil cells, an increase of ALT activity in the blood compared to children with lower BLCs. As a nutritional supplement for the rehabilitation of these children, dietary fiber from cereals of 10 g per day was used for 30 days, as an addition to main dishes and salads during lunch. As a result, BLC significantly decreased. At the same time, the number of eosinophils in blood and the activity of ALT significantly decreased. The thiol-disulfide ratio increased. Children tolerated nutritional intervention well. Its safety was also indicated by the absence of changes in indicators of the functional state of the liver. This allows us to recommend this dietary supplement for the improvement of children undergoing environmental lead pressure.

Метою дослідження було оцінити ефективність харчових волокон у зниженні підвищеної концентрації свинцю (ПКС) в крові українських дітей. Матеріали та методи. Було обстежено 80 випадково обраних дітей віком від 4 до 15 років. Вміст свинцю у венозній крові визначали методом атомно-абсорбційної спектрометрії з електротермічним розпилювачем (ЕТ ААС). Показники морфологічного та біохімічного дослідження крові визначали загальноприйнятими методами. Результати. Близько чверті дітей мали BLC ≥ 5 мкг/дл. У них був підвищений вміст еозинофільних клітин, підвищення активності АлАТ у крові порівняно з дітьми з нижчими БЛК. Як харчову добавку для реабілітації цих дітей використовували харчові волокна із злаків по 10 г на добу протягом 30 днів, як доповнення до основних страв і салатів під час обіду. У результаті BLC значно зменшився. При цьому кількість еозинофілів у крові та активність АЛТ значно знизилися. Тіол-дисульфідне співвідношення зросло. Діти добре перенесли дієтичне втручання. Про його безпечність також свідчила відсутність змін показників функціонального стану печінки. Це дозволяє нам рекомендувати цю дієтичну добавку для оздоровлення дітей, які зазнають тиску свинцю навколишнього середовища.
Hnida N. I. Dietary fiber in reducing of elevated blood lead concentration in children / N. I. Hnida, I. M. Hnidoi // PNAP. Scientific Journal of Polonia University. – 59(4). – 2023. – P. 213-220. DOI https://doi.org/10.23856/5927
Keywords: environment; public health; lead exposure; oxidative stress; rehabilitation; навколишнє середовище; громадське здоров'я; вплив свинцю; окислювальний стрес; реабілітація; Research Subject Categories::MEDICINE; Research Subject Categories::PHARMACY